VD_FINDINFO Arrêt / 2020 / 736 vom 28. August 2020 - VD Tribunal cantonal (2020)
DROIT D'OBTENIR UNE DÉCISION, DÉCISION SUR OPPOSITION, AA, PRINCIPE DE LA BONNE FOI | 29 Cst., 5 al. 3 Cst., 9 Cst., 49 LPGA, 51 LPGA, 52 LPGA